PTU-128 The efficacy of using low-fat dietary interventions to manage bile acid malabsorption. (17th June 2017) - Jackson, A; Lalji, A; Kabir, M; Muls, A; Gee, C; Vyoral, S; Shaw, C; Andreyev, J
Abstract : Introduction: Dietary fat ingestion triggers bile secretion into the gastrointestinal (GI) tract. Bile acid diarrhoea (BAD) or malabsorption (BAM) affects 1%–2% of the population. Affected individuals suffer a wide range of GI symptoms in addition to loose stool. The diagnosis is often missed and treatments are often reported to be ineffective. In this study we used SEHCAT scanning to determine treatment options and evaluated the impact of low-fat diets on GI symptoms in these patients. Method: This study analysed prospectively collected data in patients with 7 day 75 selenium homocholic acid taurine (SeHCAT) scan retention <20%. All patients reporting type 6 or 7 stool were offered a SeHCAT scan. Patients with abnormal scans requiring a bile acid sequestrant were given this before receiving dietary advice. Patients completed a 7 day food diary before consultation with a registered dietitian and personalised low-fat dietary interventions, providing 20% of daily energy from fat were prescribed. Symptoms were assessed using a modified Gastrointestinal Symptom Rating Scale questionnaire before and 4–12 weeks after dietary intervention. Results: Between January 2014 to March 2016, 114 patients, 49 men and 65 women, median age of 64 years, median BMI of 27 kg/m 2 were evaluated. 50% had previously undergone GI surgery and 45% had additional GI disorders. 44% were taking Colesevelam. After dietary intervention, the frequency with which patients experienced GI symptoms decreased, with a significant reduction in troublesome urgency, flatulence, abdominal pain, nocturnal defaecation, belching and borborygmi (p≤0.01). Stool consistency and stool frequency also improved. Conclusion: Dietary intervention is an effective treatment option for patients with symptomatic bile acid malabsorption/diarrhoea and should be routinely considered. The exact fat restriction which is effective, requires further study. Disclosure of Interest: None Declared